The aesthetic expe rience in times of tec hnological virtualization - Conte, Elaine (2016)
This essay attempts to problematize the meaning of art and technologies in the educational rationale, based on the elements of the critical aesthetic theory of Theodor Adorno. For this, we raise the following issues: Does it still make sense to think about the formative experience of art within the digital age? Is it possible to demystify the technologies of education through the aesthetic reconstruction of meanings? How can we consider the expressive dimension of education within the scope of instrumentality? Through a hermeneutic study, we seek to understand and rethink technologies, discussing a critical mediation of the universe of art in education, as a reflexive gesture, a dialogical and emancipatory exchange, at the same time made possible and yet hindered by the opposing and intense relationships of today.